Black-spotted pond frog Pelophylax nigromaculatus as a new host for the renal coccidian genus Hyaloklossia (Alveolata: Apicomplexa). (April 2022) - Tokiwa, Toshihiro; Chou, Shyun; Morizane, Riona; Yoshikawa, Natsuhiko
Abstract: Hyaloklossia Labbé, 1896 (Apicomplexa: Sarcocystidae) is a renal coccidium that infects anuran species. The genus consists of two species: H. lieberkuehni, recorded from Pelophylax kl. esculentus, Pelophylax ridibundus, and Rana temporaria in Europe; and H. kasumiensis, recorded from Pelophylax porosus porosus in Japan. However, there have been no reports of Hyaloklossia in the other anurans in Japan. On June 2021, we examined a total of 58 adult frogs comprising 2 P. p. porosus, 23 Pelophylax nigromaculatus, 8 Rana japonica, 3 Glandirana rugosa (Ranidae), 13 Fejervarya kawamurai (Dicroglossidae), and 9 Buergeria buergeri (Rhacophoridae) for infection by Hyaloklossia . Microscopic examination of kidney tissues revealed a high infection incidence of 47.8% (11/23) in P. nigromaculatus, but the other frog species were negative for Hyaloklossia . Morphological and molecular analyses using nuclear ribosomal and mitochondrial genes confirmed the infective species as H. kasumiensis. This is a new host record for H. kasumiensis. Graphical abstract: Image 1 Highlights: Hyaloklossia genus contains two parasitic coccidian species that infect anurans. A total of 58 frogs of 3 families, 5 genera, and 6 species were examined for renal coccidian parasites in Japan. We found that 47.8% of Pelophylax nigromaculatus hosted Hyaloklossia kasumiensis . All other frog species examined did not harbour Hyaloklossia infections. This is the first description of H. kasumiensis in Pelophylax nigromaculatus.